Management of epilepsy through indigenous traditional and Western approaches in Africa: A systematic review - Qolile Chabangu; Maria S. Maputle; Rachel T. Lebese (AOSIS, 2022)
Background: Reaction to epilepsy management has been described as moulded by traditional beliefs, despite the reported progress of anti-epilepsy medication. In Africa, traditional healers are seen as essential in providing epilepsy care, yet little is known about their epilepsy care. Aim: This manuscript aimed to systematically review and summarise the various indigenous traditional and Western methods of epilepsy management and their effectiveness in Africa. Setting: This study is conducted in Africa. Methods: A systematic review was performed, searching MEDLINE (through PubMed), Google Scholar and ScienceDirect data from 2000 to December 2021. The search strategies used terms and medical subject headings 'traditional methods' AND 'epilepsy' AND 'management' AND 'Africa'. The bibliography of the included articles was manually searched. Critical Appraisal Skills Programme and systematic reviews of randomised controlled trials tool were used to identify the validity of studies. Results: The search generated 17 927 articles. After screening for titles and abstracts, duplicate entries were removed and full texts of 22 articles were reviewed. After reading full texts, 12 articles met the inclusion criteria. The themes identified from synthesised data were indigenous traditional and Western methods of epilepsy management. Conclusion: Traditional and faith-based healers were perceived to provide frontline care for people living with epilepsy resulting in considerable delays in seeking anti-epilepsy medication initiation. Furthermore, taking anti-epilepsy treatment was not adequately adhered to. Contribution: Findings would contribute to the body of essential information to create awareness and upskill the community that epilepsy is like any medical condition that needs medical care.